India - China - Kundra, Ashok (New Delhi, 2009)
This comprehensive reference highlights the key differences between India and China in their policy framework and critically examines the far reaching impact of the Foreign Direct Investment (FDI) policy on trade, technology, and employment.
Keywords: "Investments,Foreign-India"